Comparison of the efficacy and safety of the EXTREME regimen for treating recurrent or metastatic head and neck squamous cell carcinoma in older and younger adult patients. Issue 2 (9th December 2020) - Fukuda, Naoki; Yunokawa, Mayu; Fujiwara, Yu; Wang, Xiaofei; Ohmoto, Akihiro; Hayashi, Naomi; Urasaki, Tetsuya; Sato, Yasuyoshi; Nakano, Kenji; Ono, Makiko; Tomomatsu, Junichi; Mitani, Hiroki; et al.
Abstract: Background: Head and neck squamous cell carcinoma (HNSCC) is a geriatric cancer. However, older adult patients are frequently underrepresented in large clinical trials. Aims: The aim of this study is to assess the efficacy and safety of the EXTREME regimen (platinum + fluorouracil + cetuximab) in older and younger adult patients with HNSCC. Methods and results: Patients with recurrent or metastatic HNSCC treated with the EXTREME regimen were retrospectively analyzed. We compare the efficacy and safety in older (aged ≥70 years) younger (aged <70 years) adult patients. Of the 86 patients examined in this study, 21 (24.4%) were older adults. There was no difference in overall response rate (46.9% vs 38.5%, P = .76), median progression‐free survival [5.7 months vs 5.8 months, hazard ratio (HR) 0.88, 95% confidence interval (CI) = 0.52‐1.51, P = .66] and overall survival (OS) (14.6 months vs 15.2 months, HR 0.79, 95% CI 0.43‐1.43, P = .44) in younger vs older patients. There was also no difference in the incidence of grade 3/4 adverse events between groups. The exploratory analysis for geriatric nutritional risk index (GNRI) showed the association with lower GNRI (≤98) and poor OS in older adult patients (37.7 months vs 7.0 months, HR 0.53, 95% CI 0.31‐0.89, P = .002). Conclusions: The EXTREME regimen with optimal dose modification is safe and effective for both older and younger adult patients with HNSCC. The GNRI can be an indicator to select the older adult patients who can get benefit from the EXTREME regimen.